Legal Studies for Spatial Planning of Urban Areas Based on Green Policy - Virda Lantika; Endang Sutrisno (Riviera Publishing, 2026)
This study discusses the study of urban spatial planning based on green policy in Kuningan Regency as a response to the challenges of sustainable development and environmental protection. The background of this research is based on the increasing pressure of land conversion, the development of tourist areas, and the incompatibility of the Kuningan Regency RTRW Regional Regulation for 2011-2031 with the current conditions and space needs. Spatial planning is an important instrument to maintain a balance between economic development, environmental sustainability, and social justice, including meeting the need for Green Open Space of at least 30% of the city area. This study uses a normative juridical approach with qualitative methods through literature study, observation and data triangulation. The theoretical framework used includes legal policy theory, legal certainty, legal effectiveness, and sustainable development. The results of the study show that green policy-based spatial planning requires RTRW policy reform that is adaptive to development dynamics, increasing the capacity of local governments, and strengthening environmental supervision and licensing instruments. The integration of spatial planning policies and environmental protection is expected to create legal certainty, the effectiveness of policy implementation, and the sustainability of the ecological function of the region. This research is expected to make a theoretical and practical contribution as the basis for the formulation of sustainable spatial planning policies in Kuningan Regency.